Pengembangan Buku Petunjuk Praktikum Lapangan Berbasis Jigsaw Sebagai Sumber Belajar Identifikasi Vertebrata - Nasrianty, Nasrianty; Pratomo, Ryan Humardani Syam (Jurnal Biotek, 2024)
This research aimed to evaluate the validity and feasibility of the Jigsaw-based field practicum guidebook as a learning resource for vertebrate identification. The development of the guidebook followed the Borg and Gall model for research-based product development. The research stages included a preliminary study and a field trial process. Based on assessments from two validators, the guidebook received an average score of 4.68, which falls within the "very good" category. The researcher conducted a limited trial with 10 students who varied in ability. The results of the limited trials showed average percentage scores of 84% (high ability), 79% (medium ability), and 77% (low ability). For the field trial, a one-group pre-test and post-test design was applied. Data analysis was performed using SPSS 23 for Windows, employing the paired t-test formula. A significance value of 0.000 was obtained from the field trial analysis, indicating a value lower than 0.05. Therefore, it can be concluded that there is a significant difference between students' pre-test and post-test scores. The results showed that the field practicum guidebook developed by the researcher is suitable for learning.